(untitled) (Journal of the College of Education for Women, 2019)
Early childhood Is the of the important stages in the life of man and initiated full on othersreliability has been rise in growth toward independence and self-reliance, as is the transitionfrom the home environment to the kindergarten environment (kindergarten) (4-6) years wherestarts in the interaction with the external environment, it is an essential stage in theconstruction of sound personal to the child, and choose proper clothes at this age is one of theimportant aspects in building the child’s personality, as it reflects the clothing behavior andtaste his parents, especially his mother, she is the first responsible for providing clothes forher children. Children at this stage are dependent the mothers in the selection of clothing, andthe clothing helps its inception and with coexistence around him, especially in the initialstages of his life, as the Almbusah habits passed down from generation and the last group toanother in the same societyIn order to achieve the desired benefit from the use of clothes should the mind physicaland social considerations by examining the different growth aspects to this stage because theyaffect as wear and what must be an element of the terms in this clothing, small does not carewho his clothing child but it does not hamper his movement and activity and acceptanceamong his peersThe study aimed to identify the extent of the mother culture in the selection of babyclothes in early childhood (4-6 years) and its relationship with some variables mother’sprofession (working - not working), the number of childrenTo achieve the objective of the study was to build a tool to measure the mother culture inthe selection of baby clothes, has adopted the questionnaire in Setup Utility For informationconducted a prospective study (50) or randomly selected from the city of Baghdad BjanbheKarkh and Rusafa, the questionnaire included an open question for a sampleQ/ What is the Almbusah and what are the foundations and rules that are in the light ofchoosing baby clothes culture?The preparation of the scale in its final form after it has been presented to the experts tocheck the validity of paragraphs or failure expired, as has been applied to a random sample(10) mothers to ensure the clarity of the instructions and paragraphs, and depending on thestability of the scale by using the run-off mode and using the Pearson correlation coefficientwas the correlation coefficient (0 0.84) is a good stability coefficientAfter that was the final application of the measure on a sample of (100) or by (50)working mother and (50) or non-functioning in Baghdad city center Bjanbhe Karkh andRusafa, emptied answers and treated statistically turned out to be mothers to have a cultureand awareness in the selection of children’s clothing stage early childhood, it turns out thatthere is a statistically significant difference in the effect of the mother culture in the selectionof baby clothes in early childhood by Mother career variable and in favor of a workingmother, it turns out that there is a statistically significant difference by a variable number ofchildren and in favor of a class (three or more children) and category ( child) At the end Findresearcher made some recommendations and proposals